Development of Customer Service Delivery System in Wholesale Trade - Kholmamatov Diyor (Indonesian Journal of Law and Economics Review, 2019)
This article describes the relationships and functions of marketing, logistics, and trade in wholesale trade services provided to wholesale consumers. Hence, development of customer service delivery system in wholesale trade was analyzed in the Republic of Uzbekistan.